THE IMPACT OF ASBESTOS WASTE ADDITION ON SOIL FOR SHALLOW FOUNDATION UNDER TRIAXIAL TESTING - Grachia Octa Viana Simanjuntak; Dandung Novianto; Marjono Marjono (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
Soil with high swelling and shrinkage properties has a low shear strength value. Such soil is certainly dangerous if used as a foundation for buildings. This research article presents asbestos waste as an alternative soil stabilizer because of the magnecium-calcium-silicat that can be used as a binder and also as a filler to fill the voids in the soil. The value of the soil shear strength parameters can be obtained from the Triaxial Unconsolidated Undrained test. The percentages of asbestos waste used are 3%, 6%, and 9% with curing periods of 0, 1, and 14 days. The results of the research show that the original soil is classified according to the USCS method as SP-SC soil with plasticity index(PI) value is 21,73%. After conducting the triaxial test on the original soil, the original soil cohesion value is 0,12 kg/cm² and the internal friction angle is 11,20°. After stabilization with several variations, it was found that the addition of asbestos waste affects the plasticity index, cohesion, and internal friction angle. Adding 9% of asbestos waste gives the maximum value of plasticity index which is 9,58%. Adding 6,37% asbestos waste with 14 days of curing provides the most optimum cohesion achieved is 0,46 kg/cm² and internal friction angle value is 27,3°. The maximum load produced by one column (Qv) is 88,80 ton, and the highest allowable loads(Qall) is 108,89 ton using a rectangular-shaped foundation(1,00 x 1,50) meter dimension. The stabilization process involved manually mixing the soil and asbestos beneath the foundation. Therefore, stabilization using asbestos waste is quite effective.